The Cambridge companion to comparative law - Bussani, Mauro; Mattei, Ugo (Cambridge : Cambridge University Press, 2012)
This title delves into the'deeper structures' of the world's legal systems, where law meets culture, politics and socio-economic factors.
Diapositives versus movies : the inner dynamics of the law and its comparative account / Mauro Bussani and Ugo Mattei -- Part I. Knowing comparative law -- Comparative law and neighbouring disciplines / Mathias Reimann -- Political ideology and comparative law / Duncan Kennedy -- Economic analysis and comparative law / Nuno Garoupa and Tom Ginsburg -- Comparative law and anthropology / Lawrence Rosen -- Comparative law and language / Barbara Pozzo -- Part II. Comparative law fields -- Comparative studies in private law / Franz Werro -- Comparative administrative law / Francesca Bignami -- Comparative constitutional law / Gunter Frankenberg -- Comparative criminal justice / Elisabetta Grande -- Comparative civil justice / Oscar G. Chase and Vincenzo Varano -- Comparative law and international organizations / George A. Bermann -- Part III. Comparative law in the flux of civilizations -- The East Asian legal tradition / Teemu Ruskola -- The Jewish legal tradition / J. David Bleich and Arthur J. Jacobson -- The Islamic legal tradition / Khaled Abou El Fadl -- The sub-Saharan legal tradition / Rodolfo Sacco -- The Latin American and Caribbean legal traditions / Diego Lopez-Medina -- Mixed legal systems / Vernon Valentine Palmer -- Democracy and the Western legal tradition / Mauro Bussani.
Includes bibliographical references and index.
Keywords: Comparative law; Legal polycentricity; Civil law